Dissecting Generalizability and Actionability of Disease-Associated Genes From 20 Worldwide Ethnolinguistic Cultural Groups - Chimusa, Emile R.; Alosaimi, Shatha; Bope, Christian D. (Frontiers in Genetics, 2022)
Findings resulting from Whole-genome sequencing (WGS) have markedly increased due to the massive evolvement of sequencing methods and have led to further investigations such as clinic actionability of genes, as documented by The American College of Medical Genetics and Genomics (ACMG). ACMG's actionable genes (ACG) may not necessarily be clinically actionable across all populations worldwide. It is critical to examine the actionability of these genes, in different populations. Here, we have leveraged a combined WES from the African Genome Variation and 1000 Genomes Project to examine the generalizability of ACG and potential actionable genes from four diseases: with high burden Malaria, TB, HIV/AIDS, and Sickle cell disease. Our results suggest that ethnolinguistic cultural groups from Africa, particularly Bantu and Khoesan have high genetic diversity, high proportion of derived allele at low minor allele frequency (0.0 - 0.1) and the highest proportion of pathogenic variants within HIV, TB, Malaria, Sickle-Cell diseases. In contrast, ethnolinguistic cultural groups from non-Africa continent, including Latin America, Afro-related, and European related groups, have a high proportion of pathogenic variants within ACG than most of ethnolinguistic cultural groups from Africa. Overall, our results show high genetic diversity at current actionable and known disease-associated genes of four African-high burden diseases, suggesting the limitation of transferability or generalizability of ACG. This supports the use of personalised medicine as beneficial to world-wide population as well as actionable gene list recommendation to further foster equitable global healthcare. The results point out the bias on knowledge about the frequencies distribution of these phenotypes and genetic variants associated to some diseases especially in African and African ancestry populations.